2x + 5y = -22 10x + 3y = 22 How can we solve this equation by elimination?
You Try…Solve by elimination –2x + 15y = –32 7x – 5y = 17 3(7x – 5y = 17) 21x – 15y = 51 –2x + 15y = –32 21x – 15y = 51 19x = 19 19 19 x = 1 7x – 5y = 17 7(1) – 5y = 17 7 –5y = 17 -7 -7 –5y = 10 –5 –5 y = –2 (1, –2)
15x + 3y = 9 10x + 7y = -4 7(15x + 3y = 9) 3(10x + 7y = –4) 105x + 21y = 63 30x + 21y = -12 -30x – 21y = 12 75x = 75 75 75 x = 1 15x + 3y = 9 15(1) + 3y = 9 15 + 3y = 9 -15 -15 3y = -6 3 3 y = -2 (1,-2)
Homework